Syrian Kurds and the Kurdish government formation project in 1934 - Tawfiq, Ali T.; Hamid, Ali S. H. (Academic Journal of Nawroz University, 2018)
The Kurds have settled in their homeland, west of Kurdistan, since ancient times. These Kurdish areas, according to travelers who visited them in different covenants, are part of Kurdistan. Syrian Kurds found themselves part of the modern Syria without taking their views and rights, yet they preserved the social fabric of the Syrian people and were promised to be the second national component after Arab nationality. According to British documents and local authorities in Iraq, France, in the early thirties of the twentieth century, worked to establish a Kurdish government in western Kurdistan by some known Kurdish figures. Although these important documents somewhat exaggerated the events by talking about the French desire to support the Kurds in Syria, these documents remain important because they shed light on events that have not been known or highlighted by the British. All in all, the study of the development of establishing a Kurdish government in western Kurdistan is worthy of knowledge and an important indicator on the development of political awareness among the Syrian Kurds during that early stage of their political history. This was remarkable after the Syrian state had become a French mandate at the time.